Studies on the provision of hosts for the mass-rearing of codling moth parasites - Theron, P. P. A.(Pieter Paul Adriaan) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1944.